Simultaneously Modeling the Supply of Weeks and Hours of Work among Female Household Heads - Blank, Rebecca M. (Journal of Labor Economics, 1988)
This paper explores the differential nature of labor-supply decisions regarding weeks of work per year and hours of work per week among female household heads. A model of labor supply that separates the weeks/hours decision is presented and estimated, allowing for simultaneity in the weeks/hours decision, as well as for the presence of either fixed costs or weeks and hours constraints. The results indicate that not only are weeks and hours decisions separate from the labormarket participation decision, but they are also quite different from each other, although they appear to be simultaneously determined.